2012
DOI: 10.1007/s00134-012-2551-y
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of critically ill lung transplant candidates on invasive respiratory support

Abstract: High-urgency LTx improves survival in critically ill intubated candidates. Higher SAPS scores, escalating therapy and an abnormal procalcitonin level were associated with a poor outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 25 publications
2
27
0
1
Order By: Relevance
“…88,[90][91][92][93]96,97,190,191 Unfortunately, a more contemporary analysis of United Network for Organ Sharing (UNOS) data cannot easily be done. By incorporating an equal weighting of urgency with posttransplantation survival in order to minimize waiting list deaths, 99 the LAS distributes scarce donated organs to those most acutely in need.…”
Section: Lung Transplantation In Copd and Life Extensionmentioning
confidence: 99%
See 3 more Smart Citations
“…88,[90][91][92][93]96,97,190,191 Unfortunately, a more contemporary analysis of United Network for Organ Sharing (UNOS) data cannot easily be done. By incorporating an equal weighting of urgency with posttransplantation survival in order to minimize waiting list deaths, 99 the LAS distributes scarce donated organs to those most acutely in need.…”
Section: Lung Transplantation In Copd and Life Extensionmentioning
confidence: 99%
“…87 Patients with COPD that have respiratory failure requiring mechanical ventilation or extracorporeal life support are a distinct group that have no reasonable expectation of sustained survival without lung transplantation. 88 Expert opinion suggests that invasive ventilatory support is a relative contraindication for lung transplantation. 23,24 However, a number of authors have reported cases and series of patients with measurable prolongation of life following transplantation in the setting of ongoing mechanical ventilation or extracorporeal life support for patients with COPD 65,[89][90][91][92] and other diseases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Overall, outcomes following lung transplantation in patients bridged with extracorporeal life support, including ECMO, have been variable, depending on the patients, their indication for transplantation, and the configuration and duration of extracorporeal support. [10][11][12][13][14] The main benefits of awake ECMO are that the patient can eat, drink, communicate, and participate in active rehabilitation, which may be an important predictor of outcome, as reported in this issue by Rehder et al 15 In theory, early use of awake ECMO may result in more physically and physiologically stable patients, as compared to those receiving invasive mechanical ventilation at the time of lung transplantation, which may translate into improved post-transplant outcomes. Indeed, some investigators have cautioned that the use of awake ECMO may lower the risk profile of recipients, resulting in a lower priority on the waiting list.…”
mentioning
confidence: 96%